Genetic characterization and regulation of the nadB locus of Salmonella typhimurium. - Cookson, B T (1987)
The nadB locus encodes the first enzyme of NAD synthesis. It has been reported that this gene and nadA are regulated by a positive regulatory protein encoded in the nadB region. In pursuing this regulatory mechanism, we constructed a fine-structure genetic map of the nadB gene. The region appears to include a single complementation group; no evidence for a positive regulatory element was found. Several mutations causing resistance to the analog 6-aminonicotinamide mapped within the structural gene and probably cause resistance to feedback inhibition. Regulatory mutations for nadB were isolated. These mutants mapped far from nadB near the pnuA gene, which encodes a function required for nicotinamide mononucleotide transport. The regulatory mutations appear to affect a distinct function encoded in the same operon as pnuA.